Drug induced exfoliative dermatitis: state of the art. Issue 1 (December 2016) - Yacoub, Mona-Rita; Berti, Alvise; Campochiaro, Corrado; Tombetti, Enrico; Ramirez, Giuseppe; Nico, Andrea; Leo, Elisabetta; Fantini, Paola; Sabbadini, Maria; Nettis, Eustachio; Colombo, Giselda
Abstract Drug induced exfoliative dermatitis (ED) are a group of rare and severe drug hypersensitivity reactions (DHR) involving skin and usually occurring from days to several weeks after drug exposure. Erythema multiforme (EM), Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are the main clinical presentations of drug induced ED. Overall, T cells are the central player of these immune-mediated drug reactions. Here we provide a systematic review on frequency, risk factors, pathogenesis, clinical features and management of patients with drug induced ED.